Analisa Hasil Tangkapan Ikan pada Bagan Perahu Berdasarkan Waktu Hauling di Perairan Ohoi Selayar Kepulaun Kei - Notanubun, Julianus; Tanjaya, Erwin; Almodar, Erna; Hukubun, Wiwi Gaby (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Bagan are classified as lift nets and use light as an attraction. Ohoi Selayar is a fish-producing center in terms of capture fisheries. Fishermen generally use bagan, in one night 3-4 times hauling with a net immersion time of 2.5-3 hours, but based on the results of our survey there is a boat bagan that operates in one night only twice hauling with a net immersion time of 4-5 hours, for this reason this research was conducted with the aim of analyzing the composition of the catch and determining the optimal hauling time for fish catches on lift net in Ohoi Selayar Waters of the Kei Islands. The method used in this research is experimental fishing method, data analysis using t test by comparing the catch of boat trawl based on hauling time. The types of fish caught on the lift net for 10 days, generally small pelagic fish species. The arrival of this type of fish is thought to be due to direct attraction by light and foraging, namely; species of Anchovy (Stolephorus sp) with a total weight of 3,020 kg (61%), Layang (Decapterus spp) weighing 1628.6 kg (33%), and squid (Loligo) 294.2 kg (6%). Based on the results of the t-test analysis comparing the total catch of the boat between hauling times I and II, the t-count of 2.525 is greater than the t- table of 1.372 at the 90% and 1.812 95% confidence levels, indicating a significant difference between hauling times I and II on the boat. Thus, technically, hauling time II of the boat chart shows an increase in catch and is effectively able to respond to the distribution of fish around the lights when compared to hauling time I.